Accessory caudal glenoid ossification centre as possible cause of lameness in nine dogs - Olivieri, M.; Piras, A.; Marcellin-Little, D. J.; Borghetti, P.; Vezzoni, A. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
An accessory centre of ossification was identified on the caudal aspect of the glenoid (ACGOC) in nine dogs. In three of the dogs, concomitant lesions were found in the same shoulder joint. When they appeared to be loose, the fragments were removed using arthroscopy in eight dogs. Upon histological examination in four dogs, the presence of articular cartilage on these ACGOC confirmed the fact that they represented a portion of the glenoid. The resolution of the clinical signs in six cases with isolated ACGOC after fragment excision and without concomitant lesions suggests that ACGOC was the cause of lameness in these affected dogs.
Keywords: Scapula; dog; shoulder joint; glenoid; accessory ossification centre; incomplete ossification; arthroscopy